2002
DOI: 10.1021/jm025555e
|View full text |Cite
|
Sign up to set email alerts
|

6-Aryl-1,4-dihydro-benzo[d][1,3]oxazin- 2-ones:  A Novel Class of Potent, Selective, and Orally Active Nonsteroidal Progesterone Receptor Antagonists

Abstract: Novel 6-aryl-1,4-dihydro-benzo[d][1,3]oxazin-2-ones were synthesized and tested as progesterone receptor (PR) antagonists. These compounds were potent and showed good selectivity for PR over other steroid receptors such as the glucocorticoid and androgen receptors (e.g., greater than 80-fold selectivity at PR for 4h). Numerous 6-aryl benzoxazinones (e.g., 4h-j) were active orally in the uterine decidualization and component C3 assays in the rats. In these in vivo models,4h had potencies comparable to mifeprist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(48 citation statements)
references
References 32 publications
0
48
0
Order By: Relevance
“…So far, nitrogen-containing heterocycles fused with an arylsubstituted benzene ring, such as compounds 3 and 4, have been widely studied. [43][44][45][46][47] Considering the structures of these non-steroidal PR ligands, we thought that bicyclic 6-arylcoumarin would be an alternative scaffold. Coumarin is one of widely used fluorophore, and the fluorescence properties of its derivatives are known to depend upon the nature and position of substituents.…”
Section: Fluorescent Progesterone Receptor Ligands Based On the Coumamentioning
confidence: 99%
“…So far, nitrogen-containing heterocycles fused with an arylsubstituted benzene ring, such as compounds 3 and 4, have been widely studied. [43][44][45][46][47] Considering the structures of these non-steroidal PR ligands, we thought that bicyclic 6-arylcoumarin would be an alternative scaffold. Coumarin is one of widely used fluorophore, and the fluorescence properties of its derivatives are known to depend upon the nature and position of substituents.…”
Section: Fluorescent Progesterone Receptor Ligands Based On the Coumamentioning
confidence: 99%
“…These might have advantages over the steroidal templates due to simpler synthetic route, and potential for greater selectivity and metabolic stability compared with steroidal templates (Dack et al, 2010;Fensome et al, 2008;Terefenko et al, 2005;Zhang et al, 2002),. With a few exceptions, these classes of agents tend to mimic the steroid A ring ketone with a cyanoaryl group isostere, as is also seen with tanaproget, the non-steroidal progestogen .…”
Section: Discovery Of Small Molecule Modulators Of Pr Functionmentioning
confidence: 99%
“…This was also true in our series, for 5 0 -cyano-2 0 -thiophene 30 retained good PR antagonist potency. 5 Compound 31, with a 5 0 -cyano-2 0 -furan group was also an antagonist, albeit somewhat weaker than 30. 5…”
mentioning
confidence: 95%
“…Previously, we showed that compound 1 (Table 1) was a potent progesterone receptor antagonist. 5 We investigated replacing the 6-(cyanophenyl) of compound 1 with 5-membered heterocyclic rings. The thiophene ring has historically been a good replacement for a phenyl ring.…”
mentioning
confidence: 99%